Density and Distribution Pattern of Red Algae Hypnea valentiae (Turner) Montague, Gametophyte and Tetrasporophyte in Tongkaina Waters, North Sulawesi and its Biomass - Deislie R.H. Kumampung; Erly Kaligis (Sam Ratulangi University, 2025)
Research on red algae Hypnea valentiae has been conducted to determine the density and distribution pattern of individual male gametophyte, female gametophyte and tetrasporophyte in Tongkaina waters. As well as its biomass. Sampling was carried out using five transect lines and five 100 cm x 100 cm squares placed along the transect lines. To determine the individual male and female gametophytes and tetrasporophytes, observations were made under a microscope. The results showed that the density of male gametophytes was 0.6 ind/m2, females gametophyte 3.36 ind/m2 and tetrasporophytes 0.72 ind/m2. All Hypnea valentiae gametophyte and tetrasporophyte individuals had a clustered distribution pattern with the wet weight of male gametophyte thallus ranging from 0.11 - 2.53 grams, females ranging from 0.23 - 4.19 grams, tetrasporophytes 0.48 - 2.07 grams. The dry weight of male gametophytes was 0.06 - 0.39 grams, females 0.03 - 0.49 grams, and tetrasporophytes 0.05 - 0.25 grams.Keywords : Hypnea valentiae gametophyte tetrasorophyte, Density, biomass Abstrak Penelitian mengenai alga merah Hypnea valentiae telah dilakukan untuk mengetahui kepadatan, dan pola penyebaran individu gametofit jantan, betina dan tetrasporofit di perairan Tongkaina. serta biomassanya. Pengambilan sampel menggunakan 5 buah garis transek dan kuadrat berukuran 100 cm X 100 cm sebanyak lima buah yang diletakkan sepanjang garis transek. Untuk penentuan individu tumbuhan gametofit jantan dan betina serta tetrasporofit dilakukan pengamatan di bawah mikroskop. Hasil penelitian menunjukkan bahwa kepadatan gametofit jantan adalah 0,6 ind/m2, betina 3,36 ind/m2 dan tetrasporotif yaitu 0,72 ind/m2. Semua individu Hypnea valentiae gametifit dan tetrasporofit mempunyai pola penyebaran mengelompok dengan ukuran berat basah thalus gametofit jantan berkisar antara 0,11 - 2,53 gram, betina berkisar 0,23 - 4,19 gram, tetrasporotit 0,48 - 2,07 gram. Berat kering gametofit jantan adalah 0,06 - 0,39 gram, betina 0,03 - 0,49 gram, dan tetrasporofit adalah 0,05 - 0,25 gram. Alga ini berpotensi besar untuk dimanfaatkan lebih lanjut semaksimal mungkin. Kata kunci: Hypnea valentiae gametofit, tetrasorofit, kepadatan, biomassa